Down syndrome: orofacial pain, masticatory muscle hypotonia, and sleep disorders - Dicieri-Pereira, Bruna [UNESP]; Gomes, Monica Fernandes [UNESP]; Giannasi, Lilian Chrystiane [UNESP]; Nacif, Sergio Roberto; Oliveira, Ezequiel Fernandes [UNESP]; Salgado, Miguel Angel Castillo [UNESP]; Amorim, Jose Benedito de Oliveira [UNESP]; Oliveira, Wagner [UNESP]; Bressane, Adriano [UNESP]; Rode, Sigmar de Mello [UNESP] (Oxford Univ Press Inc, 2022)
The aim of the present study was to investigate orofacial pain in individuals with Down syndrome (DS) and determine possible associations with masticatory muscle hypotonia (MMH), maximum mouth opening (MMO), and sleep disorders. Twenty-three individuals with DS underwent a standardized clinical examination using Axis I of the Diagnostic Criteria for Temporomandibular Disorders, for the diagnosis of pain in the masseter and temporal muscles and temporomandibular joint (TMJ). MMH was investigated using electromyography of the temporal and masseter muscles and the measurement of maximum bite force (MBF). MMO was measured using an analog caliper. Sleep disorders (obstructive sleep apnea [OSA], snoring index [SI], and sleep bruxism index [SBI]) were investigated using type II polysomnography. Statistical analysis was performed. Nonsignificant differences were found in muscle and TMJ pain between the sexes. However, myalgia and referred myofascial pain in the left masseter muscle were more frequent in males (69%) than females (40%). Electrical activity of the temporal (left: p = .002; right: p = .004) and masseter (left: p = .008) muscles was significantly lower in males than in females. MBF range was lower in males than females, indicating the highest MMH among males. OSA, SI, and SBI were identified in both sexes, but with no statistically significant differences. We concluded that myalgia and referred myofascial pain were found in some individuals with DS, especially in males. Arthralgia was found mainly in females. Temporal and masseter myalgia may have exerted an influence on the severity of MMH in males, particularly on the left side.
Keywords: Down syndrome; Facial pain; Muscle hypotonia; Masticatory muscle; Temporomandibular joint; Sleep-wake disorder